Centre-solenoid-free merging start-up of spherical tokamak plasmas in UTST. (20th February 2015) - Inomoto, M.; Watanabe, T.G.; Gi, K.; Yamasaki, K.; Kamio, S.; Imazawa, R.; Yamada, T.; Guo, X.; Ushiki, T.; Ishikawa, H.; Nakamata, H.; Kawakami, N.; et al.
Abstract: A centre-solenoid-free merging start-up scheme for spherical tokamak plasmas was developed in a University of Tokyo spherical tokamak (UTST) experiment by using outer poloidal field coils. Torus breakdown was initiated at null points and two spherical tokamak plasmas with a total current up to 80 kA were generated inductively. Their merging process provided substantial ion and electron heating by magnetic reconnection. The obtained dependence of heating on plasma current suggests that high-temperature and high-current plasma suitable for neutral beam injection is attainable under the realistic conditions in the merging start-up method.